CONSTRUCTING BEAUTY: A LINGUISTIC FEATURES ANALYSIS OF KOREAN SKINCARE ADVERTISEMENTS - Erika Ardyanti; Shanty A.Y.P.S. Duwila; Ari Astutik (Pusat Studi GESI - UWP, 2025)
This study aims to reveal the ideology of beauty constructed in Korean skincare advertisements through Norman Fairclough’s three-dimensional Critical Discourse Analysis (CDA) framework, focusing on the textual dimension. The analysis specifically examines how linguistic features in advertising texts contribute to the construction of beauty ideology within the context of gender and social inclusion. The data consist of six video advertisements from Mediheal, Nature Republic, Innisfree, Sulwhasoo, Laneige, and COSRX, collected from each brand’s official YouTube channels. Using a descriptive qualitative approach with documentation and content analysis techniques, this study identifies key linguistic features such as pronouns, evaluative adjectives, repetition, conjunctions, modality, and disjunctive phrases. The findings indicate that these linguistic strategies construct a narrow and idealized representation of beauty that emphasizes flawlessness, youthfulness, and skin perfection. Such representations implicitly marginalize alternative identities related to age, skin texture, and skin tone, thereby reinforcing non-inclusive beauty standards. From a GESI perspective, the advertisements position women as primary subjects of beauty discipline, subtly pressuring them to conform to idealized norms through continuous product consumption. This discourse reflects the intersection of capitalist and patriarchal ideologies, where women’s bodies become sites of control, normalization, and commercialization. This study concludes that Korean skincare advertisements function not only as commercial texts but also as ideological instruments that reproduce gendered expectations and social exclusion. By privileging a limited definition of beauty, these advertisements contribute to unequal power relations that shape women’s self-perception, reinforce gender bias, and constrain social inclusion in contemporary beauty culture.